Psycholinguistic Analysis on the Development of English Learning - Maharanny Setiawan Poetri; Tryana Tryana; Rizky Tazkiyatul Ummami; Denok Sunarsi (International Journal of Education, Information Technology, and Others, 2022)
This study aims to explain the analysis of psycholinguistic theory in the development of learning English. With this analysis, it will open up our space in understanding the concept of language used by humans as a communication tool. Therefore, understanding language will enable researchers to understand forms of human understanding. Language is a medium for humans to think abstractly which allows factual objects to be transformed into abstract symbols. In general, the language used by humans in any part of the world is the same because language is universal. The difference lies in the language variation. Language acquisition in humans begins when children learn to speak